Fermentation of Pediococcus pentosaceus JC30 Improves Phytochemical, Flavor Characteristics and Antioxidant Activity of Mulberry Leaves - Caiyan Meng; Jiawen Xie; Jiaqi Chen; Jiajia Xuan; Zhuoying Zeng; Minghua Lai; Xuerui Kang; Jiayun Li; Guanhui Liu; Jie Tu; Hongxun Tao (Molecules)
Mulberry leaves contain polysaccharides, phenols, alkaloids, and other active ingredients which have medicinal and edible value. In this study, fermented mulberry leaf powder was prepared by solid-state fermentation using Pediococcus pentosaceus JC30. The effects of the fermentation on the phytochemical, flavor characteristics, phenolics, and antioxidant activity of mulberry leaves were studied. The results showed that the content of γ-aminobutyric acid in fermented mulberry leaf powder (FMLP) increased by 6.73-fold and the content of phytic acid decreased by 11.16%. Ultra-high-performance liquid chromatography with quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) analysis showed that the fermentation of Pediococcus pentosaceus JC30 altered the phenolic composition of mulberry leaves, increasing the total free phenolic content by 88.43%. In particular, the contents of free phenols such as leucocyanidin, myricetin, and quercetin increased significantly and were positively correlated with antioxidant capacity. The fermentation of Pediococcus pentosaceus JC30 significantly enhanced the scavenging ability of DPPH free radicals, hydroxyl radicals, and the total reducing ability of mulberry leaves. Gas chromatography ion mobility spectrometry (GC-IMS) analysis showed that FMLP has an intense fruity and floral aroma, while having less grassy and earthy odor. The fermentation improved the phytochemical, flavor, and nutritional value of mulberry leaves, which provides more possibilities for the development of mulberry leaf products outside the sericulture industry.